Parental speech during neonatal intensive care : Is it modified by skin-to-skin contact and holding? - Aarnos, Laura (My University, 2025)
It is not known how parental skin-to-skin contact and holding affect parental speech in context of neonatal intensive care unit. This study compared the amount of maternal and paternal speech in three distinct conditions: 1) parent–infant skin-to-skin contact, 2) parent holding their infant, and 3) parent present in unit without skin-to-skin contact or holding. The study included two neonatal intensive care units in Turku University Hospital, Finland, and in Tallinn Children’s Hospital, Estonia. The unit had single-family rooms in Turku and shared patient rooms in Tallinn. Auditory environment of 85 very preterm infants was recorded for 16 hours. Simultaneously, parents documented their presence in unit, skin-to-skin contact and holding. Adult speech in the audio was analyzed using automatic tools. For each closeness condition, relative amount of maternal and paternal speech was calculated as percentage of condition time. No differences were observed in maternal or paternal speech between the closeness conditions in Turku. In Tallinn, the relative amount of maternal speech was significantly higher during skin-to-skin contact and holding than during presence without them, but no differences were found in paternal speech. Skin-to-skin contact and holding do not seem to universally affect the amount of parental speech in neonatal intensive care unit. The architecture in Tallinn could explain the finding of less maternal speech during presence without physical contact as mothers had an opportunity to rest outside the infant’s room. Alternatively, intimacy of skin-to-skin contact and holding could encourage mothers to talk more to their infants in shared patient rooms.
Keywords: parental speech, skin-to-skin contact, preterm infants, neonatal intensive care unit